Canon Law w in priestly formation. ‘Formative tradition’ and modern challenges in the light of Ratio fundamentalis institutionis sacerdotalis of 6 december 2016 - ŚWITO, LUCJAN (Prawo Kanoniczne, 2018)
On 8 December 2016, in the document entitled Ratio fundamentalis institutionis sacerdotalis, the Confederation for the Clergy updated the general norms relating to priestly formation, applicable to the whole Church. Adoption of the new norms requires the Episcopal Conferences to establish a new national programme of priestly formation. The programme should, among others, redefine the curriculum of the seminaries, considering the circumstances and the needs identified in a given country. This paper analyses the social and legal realities in the present-day Republic of Poland, indicating the most urgent problems to be considered while educating canon law alumni. Furthermore, it posits that canon law should be taught with stronger emphasis on the secular legal regulations applicable in Poland, particularly civil law and family law. The analysis also reveals a certain anachronism in the regulations governing dealings with church property.